Interconversion and reactivity of manganese silyl, silylene, and silene complexes. Issue 47 (29th October 2019) - Price, Jeffrey S.; Emslie, David J. H.
Abstract : Interconversions between manganese silylene and silene complexes are reported, including those involving the first spectroscopically observed silene complexes with an Si H substituent, and their involvement in ethylene hydrosilylation is discussed. Abstract : Manganese disilyl hydride complexes [(dmpe)2 MnH(SiH2 R)2 ] (4 Ph : R = Ph, 4 Bu : R = n Bu) reacted with ethylene to form silene hydride complexes [(dmpe)2 MnH(RHSi{CHMe)] (6 Ph, H : R = Ph, 6 Bu, H : R = n Bu). Compounds 6 R, H reacted with a second equivalent of ethylene to generate [(dmpe)2 MnH(REtSi{CHMe)] (6 Ph, Et : R = Ph, 6 Bu, Et : R = n Bu), resulting from apparent ethylene insertion into the silene Si–H bond. Furthermore, in the absence of ethylene, silene complex 6 Bu, H slowly isomerized to the silylene hydride complex [(dmpe)2 MnH({SiEt n Bu)] (3 Bu, Et ). Reactions of 4 R with ethylene likely proceed via low-coordinate silyl [(dmpe)2 Mn(SiH2 R)] (2 Ph : R = Ph, 2 Bu : R = n Bu) or silylene hydride [(dmpe)2 MnH({SiHR)] (3 Ph, H : R = Ph, 3 Bu, H : R = n Bu) intermediates accessed from 4 R by H3 SiR elimination. DFT calculations and high temperature NMR spectra support the accessibility of these intermediates, and reactions of 4 R with isonitriles or N-heterocyclic carbenes yielded the silyl isonitrile complexes [(dmpe)2 Mn(SiH2 R)(CNR′)] (7a–d : R = Ph or n Bu; R′ = o -xylyl or t Bu), and NHC-stabilized silylene hydride complexes [(dmpe)2 MnH{SiHR(NHC)] (8a–d : R = Ph or n Bu; NHC = 1, 3-diisopropylimidazolin-2-ylidene or 1, 3, 4, 5-tetramethyl-4-imidazolin-2-ylidene), respectively, all of which were crystallographically characterized. Silyl, silylene and silene complexes in this work were accessed via reactions of [(dmpe)2 MnH(C2 H4 )] (1 ) with hydrosilanes, in some cases followed by ethylene. Therefore, ethylene (C2 H4 and C2 D4 ) hydrosilylation was investigated using [(dmpe)2 MnH(C2 H4 )] (1 ) as a pre-catalyst, resulting in stepwise conversion of primary to secondary to tertiary hydrosilanes. Various catalytically active manganese-containing species were observed during catalysis, including silylene and silene complexes, and a catalytic cycle is proposed.